2018
DOI: 10.1007/s40572-018-0219-7
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Induced Pulmonary Fibrosis

Abstract: Purpose of review: The incidence of pulmonary fibrosis is increasing worldwide and may, in part, be due to occupational and environmental exposures. Secondary fibrotic interstitial lung diseases may be mistaken for idiopathic pulmonary fibrosis with important implications for both disease management and prognosis. The purpose of this review is to shed light on possible underlying causes of interstitial pulmonary fibrosis and to encourage dialogue on the importance of acquiring a thorough patient history of occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 88 publications
(108 reference statements)
1
22
0
1
Order By: Relevance
“…a-i Significantly altered (p < 0.05) microRNAs in FA and CAPs-exposed mouse serum contaminant metal mixtures, including uranium (U), arsenic (As) and vanadium (V) [4][5][6]. Metals-based exposure has been implicated in several adverse health effects, including pulmonary and cardiovascular diseases, neurological disorders and cancer [53][54][55][56]. Recent epidemiological evidence from the area has suggested cognitive deficits in Navajo children compared to the national average [57].…”
Section: Discussionmentioning
confidence: 99%
“…a-i Significantly altered (p < 0.05) microRNAs in FA and CAPs-exposed mouse serum contaminant metal mixtures, including uranium (U), arsenic (As) and vanadium (V) [4][5][6]. Metals-based exposure has been implicated in several adverse health effects, including pulmonary and cardiovascular diseases, neurological disorders and cancer [53][54][55][56]. Recent epidemiological evidence from the area has suggested cognitive deficits in Navajo children compared to the national average [57].…”
Section: Discussionmentioning
confidence: 99%
“…Aluminium encephalopathy results from the interaction of aluminium with the CNS to produce inflammation, degeneration, and demyelination [ 1 2 3 4 5 6 7 8 9 10 11 ]. Although many neurotoxins such as lead, mercury, aluminum, copper, zinc, recreational drugs, alcohol, and tobacco are present in our environment, only a few of them cause pathognomonic neurologic syndromes [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aluminium encephalopathy results from the interaction of aluminium with the CNS to produce inflammation, degeneration, and demyelination [ 1 2 3 4 5 6 7 8 9 10 11 ]. Although many neurotoxins such as lead, mercury, aluminum, copper, zinc, recreational drugs, alcohol, and tobacco are present in our environment, only a few of them cause pathognomonic neurologic syndromes [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 ]. Most of their manifestations can mimic psychiatric, metabolic, inflammatory, neoplastic and degenerative diseases of the nervous system (table 2 submitted as supplementary file 2) [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent, comprehensive literature review, Assad et al [44] evaluated clinical and mechanistic studies to try and determine the role of metals in the development of pulmonary fibrosis. The authors found that occupational and environmental exposure to numerous metals appeared to show an association with pulmonary fibrosis, including aluminium, arsenic, cadmium, copper, molybdenum, tungsten and colbalt, uranium and vanadium.…”
Section: Metal and Mineral Dustmentioning
confidence: 99%